(untitled) (Scientific journal of the Fergana State University, 2023)
The article is dedicated to clarifying the nature and artistic features of satire and humor through the analysis of comic stories of Utkir Hashimov, in particular the story “Telpak”. In the article, it is revealed on the basis of analysis that the story presents an important socio-political issue through humor and laughter. Also, the writer’s ability to clearly tell the truth of life in his story and create a comic type of the time he lived in is shown in the character of the hero of the story, Starshina Eshboyev. In the article, it is proved that the story puts forward the idea of warning a person that ignorance will lead him to this state if he does not master his profession deeply. As a result, during the analysis of the story “Telpak” by Utkir Hashimov, the aspects and methods of literary humor, the writer’s attempts to create a comic character and type, as well as the skill of using artistic image tools in creating humor were determined.